2020
DOI: 10.1523/jneurosci.1029-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

It Is All in the Right Amygdala: Increased Synaptic Plasticity and Perineuronal Nets in Male, But Not Female, Juvenile Rat Pups after Exposure to Early-Life Stress

Abstract: Early-life stress (ELS) is associated with increased vulnerability to mental disorders. The basolateral amygdala (BLA) plays a critical role in fear conditioning and is extremely sensitive to ELS. Using a naturalistic rodent model of ELS, the limited bedding paradigm (LB) between postnatal days 1-10, we previously documented that LB male, but not female preweaning rat pups display increased BLA neuron spine density paralleled with enhanced evoked synaptic responses and altered BLA functional connectivity. Sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 82 publications
3
65
1
Order By: Relevance
“…In another recent study, again, not explicitly designed to assess the stress acceleration hypothesis, Guadagno et al (2020) reported a number of effects of early life adversity. Of most direct relevance to the current study, Guadagno and colleagues reported that early life adversity increased the density of PV-labelled interneurons with a PNN, an effect that we did not observe.…”
Section: Discussionmentioning
confidence: 99%
“…In another recent study, again, not explicitly designed to assess the stress acceleration hypothesis, Guadagno et al (2020) reported a number of effects of early life adversity. Of most direct relevance to the current study, Guadagno and colleagues reported that early life adversity increased the density of PV-labelled interneurons with a PNN, an effect that we did not observe.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, early-life adverse experiences have been associated with aberrant PNN density and intensity in the adult prefrontal cortex [ 104 ], basolateral amygdala [ 105 ], and hippocampus [ 106 , 107 ], suggesting that early life stress affects PNN organization throughout the brain. It is also noteworthy that infant rats reared in stressful conditions exhibit longer retention of fear memories than standard-reared rats (for a review, see [ 7 ]), where this is accompanied by earlier maturation of GABAergic neurons and PNNs in the amygdala in male individuals [ 108 ].…”
Section: Pnns and Brain Maturationmentioning
confidence: 99%
“…However, it is important to also recognize the rapidly-growing body of work supporting changes in PNNs themselves (or their key components) in response to physiological stimuli, such as stress, exercise, environmental enrichment, diet, circadian rhythms, and normal aging processes. Short term and chronic stress lead to brain region-dependent changes in PV cells and PNNs both in early life (Castillo-Gómez et al, 2017 ; Ueno et al, 2018 ; Murthy et al, 2019 ; Guadagno et al, 2020 ; Soares et al, 2020 ; Yu et al, 2020 ) and in adults (Pesarico et al, 2019 ; Yu et al, 2020 ). Exercise also alters PNNs, and the effects are dependent on the brain region examined (Smith et al, 2015 ; Briones et al, 2021 ).…”
Section: Impact Of Physiological Stimuli On Pnnsmentioning
confidence: 99%